2023
DOI: 10.3390/nu15133009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Qualitative Changes in Diet Associated with the Consumption of Ultra-Processed Foods: A Survey on a Representative Sample of Manufacturing Workers in Brazil

Abstract: The increasing intake of ultra-processed (UP) foods is causing changes in the profile of food and nutrient consumption, negatively influencing consumer behavior. The present study aimed to evaluate the influence of UP foods on the diet of Brazilian adults, verifying the association between its increasing contribution to total energy and trends in the consumption of other NOVA groups, food subgroups, energy consumption, and macro- and micronutrients. We conducted an observational, cross-sectional study of a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…1,2 Caffeic acid (3,4-dihydroxycinnamic acid) is a significant compound in the category of phenolic acids, and it has been widely used for several pharmacological functions, 3 such as anti-inflammatory, 3 antibacterial, 4 antioxidant, 5 immune-modulatory and anticancer. 6 The German national nutrition survey (NVS) reported that an appropriate phenolic acid intake level is important to sustain a healthy diet, 7 and the average intake level of CA is 206 (mg dL −1 ); 8 hence, it is important to develop simple and effective platforms for monitoring the concentration of CA. To date, numerous traditional methods have been utilized for the determination of CA, such as gas chromatography (GC-MS), 9 liquid chromatography (LC-MS), 10 ultra-performance liquid chromatography (UPLC), 11 mass spectroscopy, electrophoresis 12 and electrochemical detection methods.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Caffeic acid (3,4-dihydroxycinnamic acid) is a significant compound in the category of phenolic acids, and it has been widely used for several pharmacological functions, 3 such as anti-inflammatory, 3 antibacterial, 4 antioxidant, 5 immune-modulatory and anticancer. 6 The German national nutrition survey (NVS) reported that an appropriate phenolic acid intake level is important to sustain a healthy diet, 7 and the average intake level of CA is 206 (mg dL −1 ); 8 hence, it is important to develop simple and effective platforms for monitoring the concentration of CA. To date, numerous traditional methods have been utilized for the determination of CA, such as gas chromatography (GC-MS), 9 liquid chromatography (LC-MS), 10 ultra-performance liquid chromatography (UPLC), 11 mass spectroscopy, electrophoresis 12 and electrochemical detection methods.…”
Section: Introductionmentioning
confidence: 99%